The effect of particulate reinforcement addition to latent heat and solid fraction During Solidification Metal Matrix composite produced by permanent casting - Nanang, Fatchurrohman; S., Sulaiman; M.K.A., Ariffin; A.A., Faieza (Universiti Malaysia Perlis, 2010)
Organized by School of Materials Engineering & Sustainable Engineering Research Cluster, 1st - 2nd December 2009 at Putra Brasmana Hotel, Kuala Perlis, Perlis.